Experimental study on the shrinkage characteristics and devolatilization time of wood in a turbulent fluidized bed combustor using computed tomography. (15th December 2017) - Fang, Dong-dong; Chen, Jia; Zhang, Li-hui; Duan, Feng; Wang, Ping; Chyang, Chien-Song
Abstract: Computed tomography (CT) was used to scan the samples obtained from devolatilization in a turbulent fluidized bed combustor (FBC). The evolution of three-dimensional shrinkages at different residence time was measured and visualized successfully without destroying the sample. The effects of the bed temperature, and the fuel species on the mass conversion, devolatilization time, and shrinkage characteristics were also investigated. Four common Chinese wood types, poplar, Chinese fir, oak, and teak were used. The results show that the shrinkage and mass conversion increase with increasing residence time. In addition, the devolatilization time and final tangential and radial shrinkages decrease with increasing bed temperature. The final longitudinal shrinkage shows an inverse trend compared with the other two shrinkages. The tangential shrinkage is slightly greater than the radial shrinkage and much greater than the longitudinal shrinkage for all tests. Poplar wood as a kind of cork, which has the highest volatile matter content among the four woods, showed the maximum final shrinkages. Highlights: The shrinkage characteristic of four woods during devolitilization in FBC was studied. The shrinkage evolution was visualized without destroying the sample using CT method. Tangential and radial shrinkages are much higher than longitudinal one in all tests. Poplar shows the maximum shrinkages due to the wood type and higher volatile content.